Brief Report: Main Contribution of DRB1*04:05 Among the Shared Epitope Alleles and Involvement of DRB1 Amino Acid Position 57 in Association With Joint Destruction in Anti–Citrullinated Protein Antibody–Positive Rheumatoid Arthritis. Issue 7 (July 2015) - Terao, Chikashi; Yano, Koichiro; Ikari, Katsunori; Furu, Moritoshi; Yamakawa, Noriyuki; Yoshida, Shinji; Hashimoto, Motomu; Ito, Hiromu; Fujii, Takao; Ohmura, Koichiro; Yurugi, Kimiko; Miura, Yasuo; et al.
<x xml:space="preserve">Abstract</x> Objective The shared epitope is associated with increased joint destruction in rheumatoid arthritis (RA) as well as susceptibility to RA and the production of anti–citrullinated protein antibody (ACPA). However, previous studies addressing whether the association of the shared epitope with joint destruction is independent of ACPA have shown different results in different populations. Different allele distributions in the shared epitope may explain this ethnic heterogeneity. This study was undertaken to assess the associations of the shared epitope and HLA–DRB1*04:05, the most common shared epitope allele in the Japanese population, with joint destruction in patients with ACPA‐positive RA. Methods A total of 861 patients with ACPA‐positive RA who had not received any biologic agents were recruited from the institute of Rheumatology, Rheumatoid Arthritis cohort (sets 1 and 2) and the Kyoto University Rheumatoid Arthritis Management Alliance cohort (set 3). Joint destruction was assessed using the modified Sharp/van der Heijde score (SHS). The associations of the shared epitope alleles, HLA–DRB1*04:05, and other shared epitope allele groups with the SHS were analyzed in a linear regression analysis. Amino acid variations associated with the SHS were also analyzed. Results The shared epitope was significantly associated with an increased SHS (P = 0.0017). Although HLA–DRB1*04:05 was significantly associated with an increased SHS (P = 2.7 × 10−5), the group of other shared epitope alleles, including HLA–DRB1*01:01, did not show an association with the SHS in spite of sufficient power (P = 0.67). HLA–DRB1*04:05 was associated with joint destruction in a dose‐dependent manner. Analyses of amino acid associations of HLA–DRB1 revealed that serine at position 57, recently shown to have a susceptibility effect for ACPA‐positive RA in Asian populations, showed a significant association (P = 5.0 × 10−6). Conclusion HLA–DRB1*04:05, characterized by serine at position 57, accounts for the detrimental association between the shared epitope and SHS in Japanese patients with ACPA‐positive RA.